Circular Supply Chain Management in Developing Countries: Challenges, Opportunities and Pathways to Sustainability - Azmi, Fadhlur Rahim; Roni, Mastura; Sa’at , Megawati (Information Management and Business Review, 2024)
This paper offers a comprehensive exploration of circular supply chain management (CSCM) in the context of developing countries, unveiling a multifaceted landscape of challenges, opportunities, strategies and future prospects. Challenges facing these nations in embracing CSCM include a lack of waste infrastructure, limited awareness and education, financial constraints, a shortage of technical expertise, barriers to accessing global markets, and a dearth of data and information. These challenges underscore the need for tailored, context-specific solutions to establish a robust foundation for CSCM. The study looks ahead and predicts that soon there will be more circular business models, less waste management and more resource optimization, more local circular ecosystems, and more streamlined circular supply chains. Technological advancements, such as blockchain, the Internet of Things (IoT) and data analytics, are poised to revolutionize CSCM. Increased global awareness of environmental issues and sustainability will be a driving force for change, with academia, businesses, and governments playing pivotal roles in shaping this future. This paper emphasizes the pivotal role of CSCM in advancing sustainable development, both in developing countries and globally. It underscores the critical importance of a steadfast commitment to sustainability, circularity, and responsible resource management for the future of these nations and the entire planet